Mutual impacts between energy transition and maritime transportation - Yin, Yuwei (Nanyang Technological University, 2022)
Nowadays, countries globally devote efforts to facilitate energy transition, which is defined as long-term structural changes in energy consumption patterns. Many countries currently focus on substituting coal with natural gas and non-fossil fuels. The future energy system will have renewables as the core, but natural gas, as the cleanest fossil fuel, will also play a key role in stabilizing power systems, providing heat supplies, and serving as a cost-effective interim alternative transportation fuel. A literature review reveals that no study has systematically bridged the links between energy transition and maritime transportation. To fill the void, this research starts with assessing how the energy transition of a nation impacts its energy shipping import. China is selected for case studies because it is the world’s largest coal consumer as well as greenhouse gas emitter and experiences rapid energy transition. Firstly, it evaluates how policies and commercial strategies facilitating the coal-to-gas transition of China impacted its Liquefied Natural Gas (LNG) shipping import based on Vector Error Correction Modelling (VECM). It found that energy companies compromised cost-effectiveness to secure steady LNG supplies from a small group of exporters, while alternative supply expansions (i.e. expansions of domestic gas production and pipeline gas import) also had limited efficiencies to reduce LNG shipping import volumes. Secondly, this research assesses how the coal-to-gas transition impacted LNG shipping import via the Straits of Malacca and Singapore (SOMS), which supports 40% of global trades. VECM models are built to compare LNG and crude oil shipping import of China via SOMS, showing that, as crude oil demand growths were slower and less impacted by energy transition, crude oil imports via SOMS were more flexible with diversified origins and uncompromised cost-effectiveness. Thirdly, a System Dynamics (SD) model simulates LNG shipping import volumes and patterns of China until 2030, showing that growths in LNG import and the reliance on SOMS are expected to slow down in 2021-2025 due to COVID-19 and climate pledges, but will accelerate after 2025 under demand growths. Subsequently, this study investigates whether supply chain bottlenecks brought by the shipping sector also have impacts on energy transition of the nation. Two LNG supply chain bottlenecks are evaluated based on an elaborated SD model from the previous study: (1) LNG terminal capacity of China fails to accommodate LNG import volumes under any consumption growth or alternative supply reduction by 5% from the baseline scenario; (2) domestically owned LNG tanker fleet capacity, even in the baseline scenario, can only carry less than half of LNG import volumes to China, implying supply disruptions risks and limited control over import costs. Finally, this research investigates energy transition within the shipping sector. It integrates SD with a Stackelberg game to assess whether government financial supports are necessary to alter ship owners’ decisions to adopt newbuild ships powered by alternative fuels and the expected payoffs at certain government expenditure levels. The container shipping sector of Singapore is selected for the case study because the nation has large ship traffic and policy instruments to support LNG adoption. Under Singapore’s mechanism, the study reveals that financial supports are needed for container ships over 5,000 twenty-foot equivalent units before 2027. This thesis presents a useful reference for policy makers and commercial stakeholders to assess energy transition impacts on shipping, design energy strategies and facilitate energy transition.